Glee. The complete third season [videorecording (DVD)] - Murphy, Ryan, 1965-; Brennan, Ian; Falchuk, Brad; Lynch, Jane, 1960-; Michele, Lea; Morrison, Matthew, 1978- (20th Century Fox, 2012)
The Gleeks are headed for the Nationals and graduation. Younger members join New Directions, and others are about to begin new lives outside it.